MODEL OPTIMALISASI KINERJA PADA USAHA KECIL MENENGAH (UKM) BERBASIS AGRIBISNIS (Studi Kasus UKM Makanan) DI KABUPATEN OKU (JASEP, 2015)
Research models to optimize the performance of the small and medium enterprises (SMEs) in Ogan Ogan Ulu, a study that aims to obtain an effective and efficient performance for the assignment of labor on SME food is bread, soybean, coffee powder, chips, tofu and crackers. The results of the study were obtained showed that the assignment of manpower one (TK1) in SMEs tempeh, labor two (TK2) on SMEs crackers, labor three (TK3) on SMEs chips, labor four (TK4) on SMEs bread, energy work five (TK5) on SMEs know, as well as the labor of six (TK6) on SME coffee powder, with a minimum value of an index that can be obtained by SMEs to employ labor at each SMEs amounted to 499,000.